PENGARUH SiLPA DAN FISCAL STRESS TERHADAP BELANJA MODAL PADA KABUPATEN/KOTA DI PROVINSI SULAWESI TENGGARA - Muhamad Armawaddin; Muhammad Syarif; Veronika Sambo Bungin (Universitas Halu Oleo, 2020)
This study aims to examine the effect of SiLPA and fiscal stress on capital expenditure in districts and cities in Southeast Sulawesi Province. The analytical method used in the study was performed using panel data regression using Eviews 10. The data used in the study were secondary data in the form of PAD, capital expenditure, total regional expenditure, and the previous year's SiLPA. Data obtained from documentation belonging to the DJPK of the Ministry of Finance. The results obtained indicate that statistically, the SiLPA and the fiscal stress simultaneously influence capital expenditure. In part, the SiLPA has a significant positive effect on capital expenditures, while the fiscal stress has a significant negative impact on capital expenditures